Synchronization of Coupled Chaotic Systems with Ring Connection Based on Special Antisymmetric Structure - Xiangyong Chen; Jianlong Qiu; Qiang Song; Ancai Zhang (Abstract and Applied Analysis)
This paper considers the complete synchronization problem for coupled chaotic systems with ring connections. First, we use a direct design method to design a synchronization controller. It transforms the error system into a stable system with special antisymmetric structure. And then, we get some simple stability criteria of achieving the complete synchronization. These criteria are not only easily verified but also improve and generalize previous known results. Finally, numerical examples are provided to demonstrate the effectiveness of the theoretical analysis.